Beneficial effects of curtailing immune susceptibility in an Alzheimer’s disease model - Di Benedetto, Giulia (J Neuroinflammation, 2019)
BACKGROUND: Currently, there are no effective therapeutic options for Alzheimer’s disease, the most common, multifactorial form of dementia, characterized by anomalous amyloid accumulation in the brain. Growing evidence points to neuroinflammation as a major promoter of AD. We have previously shown that the proinflammatory cytokine TNFSF10 fuels AD neuroinflammation, and that its immunoneutralization results in improved cognition in the 3xTg-AD mouse. METHODS: Here, we hypothesize that inflammatory hallmarks of AD might parallel with central and peripheral immune response dysfunction. To verify such hypothesis, we used a triple transgenic mouse model of AD. 3xTg-AD mice were treated for 12 months with an anti-TNFSF10 antibody, and thereafter immune/inflammatory markers including COX2, iNOS, IL-1β and TNF-α, CD3, GITR, and FoxP3 (markers of regulatory T cells) were measured in the spleen as well as in the hippocampus. RESULTS: Spleens displayed accumulation of amyloid-β(1–42) (Aβ(1-42)), as well as high expression of Treg cell markers FoxP3 and GITR, in parallel with the increased levels of inflammatory markers COX2, iNOS, IL-1β and TNF-α, and blunted IL-10 expression. Moreover, CD3 expression was increased in the hippocampus, consistently with FoxP3 and GITR. After chronic treatment of 3xTg-AD mice with an anti-TNFSF10 antibody, splenic FoxP3, GITR, and the above-mentioned inflammatory markers expression was restored to basal levels, while expression of IL-10 was increased. A similar picture was observed in the hippocampus. Such improvement of peripheral and CNS inflammatory/immune response was associated with decreased microglial activity in terms of TNFα production, as well as decreased expression of both amyloid and phosphorylated tau protein in the hippocampus of treated 3xTg-AD mice. Interestingly, we also reported an increased expression of both CD3 and FoxP3, in sections from human AD brain. CONCLUSIONS: We suggest that neuroinflammation in the brain of 3xTg-AD mice triggered by TNFSF10 might result in a more general overshooting of the immune response. Treatment with an anti-TNFSF10 antibody blunted inflammatory processes both in the spleen and hippocampus. These data confirm the detrimental role of TNFSF10 in neurodegeneration, and corroborate the hypothesis of the anti-TNFSF10 strategy as a potential treatment to improve outcomes in AD. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12974-019-1554-9) contains supplementary material, which is available to authorized users.